Pengaruh Aromaterapi Mawar Terhadap Nyeri Persalinan: Systematic Literature Review - Friskha Irnanda Herdiani Yuana; Lisa Trina Arlym; Yocki Yuanti (Universitas Baiturrahim, 2023)
Childbirth is an emotional experience encompassing physiological and psychological mechanisms undergone by pregnant women. Labor pain is one of the most commonly complained about experiences. The purpose of this study was to determine the effect of rose aromatherapy on labor pain. This research utilized the Systematic Literature Review method. Article searches were conducted on Google Scholar, PubMed, ProQuest, and GARUDA databases from 2017 to 2022, and the selection process employed the PRISMA diagram. Inclusion criteria encompassed research articles from 2017 to 2022 discussing the impact of rose aromatherapy on reducing labor pain, involving pregnant women participants, and available in English or Indonesian. Exclusion criteria included articles irrelevant to rose aromatherapy usage, insufficient information, inappropriate language, focusing on other essential oils, and irrelevant samples. The study yielded three articles demonstrating that rose aromatherapy can alleviate pain during labor. From these three articles, the utilization of rose aromatherapy has been shown to reduce the frequency of labor pain. Usage frequency of 3-4 drops mixed with 20-40 ml of water and ignited for 10-15 minutes during the active phase of labor (Phase I) was recommended. The study concludes that rose aromatherapy has an impact on reducing labor pain in delivering mothers, especially during Phase I. Rose aromatherapy can reduce the frequency of labor pain when applied at a minimum frequency of 4 drops mixed with 40 ml of water and ignited for 15 minutes during Phase I of active labor. Based on the results of this study, it is suggested that the appropriate usage frequency of rose aromatherapy during Phase I of active labor can serve as an effective alternative for alleviating labor pain in delivering mothers.